Partial cystectomy for the treatment of spleen cysts in children - V.P. Prytula; D.Yu. Krivchenya; A.S. Kuzyk; S.F. Hussaini; M.I. Silchenko (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2020)
Introduction. There are various methods of organsaving operations on spleen with its cystic lesions, both laparotomic and laparoscopic access are widely proposed and discussed in literature. Indications, contraindications, advantages and disadvantages of trauma and reliability of each method of surgery for spleen cysts (SC) in children are discussed. Aim: To develop indications and evaluate effectiveness of partial cystectomy in surgical treatment of SC in children. Materials and methods. We analyzed 265 children with SC from whom we operated 175 (66.04%) from 1998 to 2019. The remaining 90 (33.96%) patients were monitored dynamically. A detailed analysis was conducted to determine indications and evaluate effectiveness of partial cystectomy with capitanization and without capitanization for surgical treatment of SC in children by laparoscopic and laparotomy method. Results and discussion. We performed 119 (68.00%) laparotomy and 56 (32.00%) laparoscopic interventions in children with different segmental localization of SC. Laparotomic partial cystectomy was performed in 12, partial cystectomy with capitanization - 35. Laparoscopic partial cystectomy was performed in 30, partial cystectomy with capitanization - in 21 patients with SC. Relapses after laparotomy SC correction in the area of helium by partial cystectomy with capitanization were observed in 2 (1.68%) children, in whom we performed partial cystectomy with capitanization with laparotomy. In 3 (5.36%) patients after laparoscopic partial resection of cysts without capitanization (n=2) and after partial resection of the cyst the cavity was filled with omentum (n=1), recurrences of cysts operated laparoscopically (n=1) and laparotomy (n=2). In 9 (7.56%) children after laparotomy and in 7 (12.50%) after laparoscopy, minimal residual cyst cavities were preserved, which resolved automatically in course of 1-2 years. Conclusions: Depending on localization, size, nature of parenchymal lesions in children with SC, partial cystectomy may be better choice. In order to close or minimize the volume of residual cyst, partial cystectomy should be supplemented with capitanization. Partial cystectomy with or without capitanization, taking into account its segmental blood supply by laparoscopic or laparotomy method is a rational method for treatment of SC, which radically eliminates pathology and preserves all important functions of spleen. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of all participating institution.